Prescribing tailored home exercise program to older adults in the community using a tailored self-modeled video: A pre-post study - Vaz, Sharmila; Hang, Jo-Aine; Codde, Jim; Bruce, David; Spilsbury, Katrina; Hill, Anne-Marie (Frontiers in Public Health, 2022)
Background Community rehabilitation for older people after hospital discharge is necessary to regain functional ability and independence. However, poor adherence to exercise programs continues to hinder achieving positive health outcomes in older people. This study aimed to evaluate the effectiveness of prescribing a tailored video self-modeled DVD-HEP for six weeks, on functional mobility, physical activity, exercise self-efficacy, and health-related quality of life, in a sample of frail older adults Materials and Methods A pre-test and post-test intervention study design was conducted, with each participant acting as their own control. A convergent, parallel, mixed-methods approach involving quantitative and qualitative data collection was used. Participants received an individualized assessment at baseline and subsequently were provided with a 30-minute tailored six-week self-modeled DVD-HEP that showed the physiotherapist instructing the participant. The physiotherapist phoned participants fortnightly to encourage engagement in the program and explore responses to it. Outcomes evaluated included functional mobility, balance, gait speed, and exercise self-efficacy. Results Participants (n = 15) showed clinically meaningful improvements at follow-up compared to baseline in functional mobility (TUG MCID = 3.4 to 3.5 sec, 3-MWT MCID = 0.1 to 0.2 meters/sec) and gait speed (3-MWT MCID = 0.1 to 0.2 meters/sec). There were also significant improvements in balance and self-efficacy for exercise and a 2.5-fold and a 1.3-fold increase in moderate and light physical activity participation at follow-up compared to baseline. The deductive themes were: (i) Enjoyment, self-efficacy, and well-being; (ii) Achieving life goals; (iii) Background music as a motivator to adherence; and (iv) Enhanced motor performance and learning: Task goal mastery, multimodal feedback, autonomy to self-regulate learning. The new inductive theme was (v) Preference for in-person support for exercise. Conclusion Future studies are warranted to compare a tailored self-modeled video HEP to face-to-face programs and other digital health modalities to evaluate older adults' adherence levels and functional improvement.